A Matter of State: Diversity in Oligodendrocyte Lineage Cells. (April 2022) - Kamen, Yasmine; Pivonkova, Helena; Evans, Kimberley A.; Káradóttir, Ragnhildur T.
Oligodendrocyte precursor cells (OPCs) give rise to oligodendrocytes which myelinate axons in the central nervous system. Although classically thought to be a homogeneous population, OPCs are reported to have different developmental origins and display regional and temporal diversity in their transcriptome, response to growth factors, and physiological properties. Similarly, evidence is accumulating that myelinating oligodendrocytes display transcriptional heterogeneity. Analyzing this reported heterogeneity suggests that OPCs, and perhaps also myelinating oligodendrocytes, may exist in different functional cell states. Here, we review the evidence indicating that OPCs and oligodendrocytes are diverse, and we discuss the implications of functional OPC states for myelination in the adult brain and for myelin repair.